Health implications of night and shift work on hotel workers - Júlio Roberto Ramos; Ana Paula Costa (European Journal of Tourism, Hospitality and Recreation, 2026)
Abstract Night work has existed since the dawn of humankind and, to keep up with the development of today’s society, it has become increasingly common. Traditionally, the hospitality and tourism sectors are labourintensive workplaces, which means they are particularly exposed to night and shift work. Working when the human being is physiologically designed to rest leads to lower performance and greater difficulty concentrating, making night work a risk factor for workers. Employees of four- and five-star hotel establishments are particularly prone to this type of schedule. The aim of this research is to answer the following questions: Are there health implications for hotel workers who work the night shift?; and ‘Are there safety implications for hotel workers who work the night shift?’ To this end, this study utilized a quantitative methodology. A questionnaire was used as a data collection tool and was completed by a sample of 111 workers from two 4- and 5-star hotels. Night workers feel that night work has an impact on their health, their safety and productivity. The perception of the negative impact that night work has on the health and safety of hotel workers was confirmed, in line with the existing literature.